Development of novel biofilm using Musa acuminata (waste banana leaves) mediated biogenic zinc oxide nanoparticles reinforced with chitosan blend - Sasidharan, Shivitraloshini; Tey, Lai-Hock; Djearamane, Sinouvassane; Mahmud Ab Rashid, Nor Khaizura; PA, Raajeswari; Shing Wong, Ling; Tanislaus Antony Dhanapal, Anto Cordelia (Elsevier, 2024)
Objectives: The present study reports a cost-effective, eco-friendly, and straightforward approach to synthesize Zinc Oxide Nanoparticles (ZnO NPs) using agro-waste banana (Musa acuminata) leaves and compares it with chemogenic ZnO NP. Methods: The study investigated biogenic and chemogenic ZnO NPs, examining their size, shape, morphological structure, and stability using UV–Vis Spectroscopy, X-Ray Diffraction (XRD), Field Transmission Scanning Electron Microscopy (FESEM), Energy Dispersive X-Ray (EDX), and Fourier Transform Infrared Spectroscopy (FTIR). Antibacterial potency against Staphylococcus aureus and Salmonella typhimurium was tested through the Disk Diffusion method. Bio-nanocomposites were created by incorporating different ZnO NP concentrations into chitosan via the solvent casting method. Film characteristics were analyzed using SEM, tensile strength, film moisture (FM), film solubility (FS), and water-holding capacity (WHC). Antibacterial activity of the bio-nanocomposites was assessed against Staphylococcus aureus and Salmonella typhimurium using the Viable Cell Colony Count method. Results: The results of color change confirmed the formation of biogenic and chemogenic ZnO NP having sharp peaks at 370 nm and 381 nm respectively having spherical structure with an average crystalline size of 36.73 nm and 75.31 nm. The biogenic ZnO NP had greater inhibitory action against both Staphylococcus aureus and Salmonella typhimurium than chemogenic ZnO NP. Besides, the biogenic biofilms had enhanced characteristics followed by chemogenic and chitosan biofilms. Conclusion: The study suggests a green approach, using smaller nanosized biogenic ZnO NPs with unique advantages over chemogenic counterparts. The resulting biofilms exhibit the potential to enhance food quality, safety, and longevity in the food industry. This aligns with circular green economy principles, utilizing waste banana leaves for raw material synthesis and promoting manufacturing innovation.